Strategic capacity withholding through failures in the German-Austrian electricity market - Julian Bergler; Sven Heim; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
In electricity day-ahead markets organized as uniform price auction, a small reduction in supply in times of high demand can cause substantial increases in price. We use a unique data set of failures of generation capacity in the German-Austrian electricity market to investigate the relationship between electricity spot prices and generation failures. Differentiating between strategic and non-strategic failures, we find a positive impact of prices on non-usable marginal generation capacity for strategic failures only. Our empirical analysis therefore provides evidence for the existence of strategic capacity withholding through failures suggesting further monitoring efforts by public authorities to effectively reduce the likelihood of such abuses of a dominant position.
urn:nbn:de:bsz:180-madoc-406401
Keywords: L94; L12; L41; K21; 330; Antitrust Policy; Market Power; Auctions; Electricity; Withholding